2017
DOI: 10.1080/10942912.2017.1396479
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic and structural properties of ovalbumin treated by pulsed electric fields

Abstract: In this study, the immunogenic and structural properties of ovalbumin (OVA) induced by pulsed electric fields (PEF) treatment were investigated. The immunogenic properties were estimated by the IgG and IgE binding abilities, which were determined by enzyme-linked immunosorbent assay (ELISA) using rabbit polyclonal antibodies and egg-allergy patients' sera, respectively. The structural changes were monitored by circular dichroism (CD), ultraviolet absorption, and fluorescence spectroscopy. When the OVA samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 36 publications
(51 reference statements)
0
24
2
Order By: Relevance
“…Preheating treatment induced the conformation of ovalbumin to partially unfold, reflecting in the increase in β-sheet and β-turn contents and the reduction in the total amount of α-helix and random coil, intrinsic fluorescence intensity, and surface hydrophobicity. At present, studies have shown that linear IgG and IgE epitopes were transmitted through the entire amino acid sequence of ovalbumin. , The partial unfolding aroused via preheating treatment may lead to the exposure of linear and structural IgG and IgE epitopes originally masked in ovalbumin molecules. Therefore, H-Oval was insignificantly enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…Preheating treatment induced the conformation of ovalbumin to partially unfold, reflecting in the increase in β-sheet and β-turn contents and the reduction in the total amount of α-helix and random coil, intrinsic fluorescence intensity, and surface hydrophobicity. At present, studies have shown that linear IgG and IgE epitopes were transmitted through the entire amino acid sequence of ovalbumin. , The partial unfolding aroused via preheating treatment may lead to the exposure of linear and structural IgG and IgE epitopes originally masked in ovalbumin molecules. Therefore, H-Oval was insignificantly enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…Both interactions with epigallo‐catechin 3‐gallate and chlorogenic acid reduced IgE‐binding capacity of ovalbumin, due to the shielding of the linear IgE epitope (Lu et al., 2018; Ognjenović et al., 2014). Pulsed electric field treatment > 25 kV/cm (for 180 µs) or at 35 kV/cm for long time (>60 µs) was proven to reduce the IgE binding of ovalbumin, due to aggregate formation (Yang, Zhang et al., 2017).…”
Section: Effect Of Processing On Allergenicity Of Eggmentioning
confidence: 99%
“…Different food processing methods, such as boiling [9,10], autoclaving [11], extrusion [12], microwave [13], pulsed-electric field [14], ultrasound [15], and HHP [16,17], may alter the intrinsic structure of food proteins and, consequently, decrease their allergenic properties. These processes may be coupled to enzymatic hydrolysis to further decrease the allergenicity of a wide range of conventional food proteins and generate protein hydrolysates that could potentially be integrated into specific formulations for food-allergic patients [18].…”
Section: Introductionmentioning
confidence: 99%